Technology-assisted sheltered instruction: instructional streaming video in an EFL multi-purpose computer course. Issue 3 (2nd April 2016) - Huang, Yun-Hsuan; Chuang, Tsung-Yen
Abstract : Content-based instruction (CBI) has been widely adopted for decades. However, existing CBI models cannot always be effectively put into practice, especially for learners of lower English proficiency in English as a foreign language (EFL) context. This study examined an animation design course adopting CBI to promote reading abilities of English majors at a technology university in Taiwan. CBI usually adds challenges in cognitive and linguistic learning, especially for English majors in computer courses. Different from other CBI courses, this course dealt with multiple situations: multi-approaches (CBI and task-based instruction); multi-skills (Flash animation software skills- various animation effects; language skills-computer vocabulary and reading comprehension); multi-level learners (various English language proficiency levels – mostly low proficiency level; computer abilities; learning styles), and a large class taught by one instructor. Simply employing CBI cannot solve such complex problems. Therefore, instructional streaming video was applied as a learner-directed scaffold and a technological facilitator. A control group and an experimental group comprised 117 and 121 English majors taking this course for one semester respectively. Both groups were taught with English materials but the later were additionally provided with instructional streaming video (ISV). Qualitative and quantitative data were collected from classroom observations, interviews, exams, and semester-end questionnaires from both groups to examine whether ISV facilitated instructor teaching and student learning. Results show that the experimental group significantly performed better in reading comprehension, reading speed, acceptance, attention, and exams, as well as easing teaching difficulties. Drawn upon empirical results, a technology-assisted sheltered model was generated for EFL multi-purpose courses.